Ecuadorian adolescents with high and low levels of school refusal for the search for the attention of other significant people and their differences with perfectionism - Virginia Narcisa Ortega Sandoval; Mª Pilar Aparicio Flores; Aitana Fernández Sogorb; José Manuel García Fernández (INFAD, 2019)
Several investigations summarize perfectionism as a set of clearly negative features which is especially worrying in the adolescence stage due to peer and family pressure at social, academic, sports and cultural levels among others, an issue that becomes a feature pathological. On the other hand, there is a group of children and young people who refuse to go to school in order to get the attention of others. That is, it creates anxiety for the separation of the family figure. In the present study, it was intended to observe if there are statistically significant differences in perfectionism with Ecuadorian adolescents with high and small scores in the pursuit of attention from significant others. For this, the Child-Adolescent Perfectionism Scale (CAPS) and the School Refusal Assessment Scale-Revised for Children (SRAS-R-C) were used. The total sample of participants was 1920 adolescents aged between 15 and 18 enrolled in courses between 1st and 3rd Baccalaureate. The differences found are found in both school rejection groups for Socially Prescribed Perfectionism (SPP), Self-Oriented Perfectionism-Strivings (SOP-S) and Self-Oriented Perfectionism-Critical (SOP-C), with the students with the highest level of school rejection those who scored highest in SPP (d = .17), SOPS (d = .15) and SOP-C (d = .35). In this regard, it is necessary to expand research in this field of study taking into account the vulnerability in adolescents’ personality and the association with a multitude of psychopathological disorders with which perfectionism correlates according to previous literature.